PENCEGAHAN KEMUNCULAN RADIKALISME DI ERA POST-TRUTH MELALUI SOSIALISASI LITERASI MEDIA DI DESA PESANTREN KEDIRI - Nurul Dwi Lestari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
Social media is a new phenomenon that is followed by modern society. The public needs to know that behind the freedom of social media as a means of self-expression of opinion, there are various domains of rules and ethics that must be met. The purpose of this community service is to describe the implementation of community service activities to prevent the emergence of radicalism in the post-truth era through media literacy socialization in the Pesantren Village, Kediri City. The specific objectives of this study are to describe: (1) the public's view of radicalism in the post-truth era, and (2) the implementation of media literacy socialization to prevent radicalism in the post-truth era. This community service method uses the Participatory Action Research (PAR) method by involving community participation to encourage better action. Media literacy socialization in the Pesantren Village, Kediri City discussed four efforts to prevent radicalism due to hoax news, including (1) reopening the village library equipped with facilities for accessing the internet wisely, (2) creating discussion groups on social media as a means of communication that